1997
DOI: 10.4095/209171
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomy and biostratigraphy of Middle and Late Triassic elasmobranch ichthyoliths from northeastern British Columbia

Abstract: Diverse and abundant Middle and Late Triassic elasmobranch ichthyoliths (microscopic shark teeth and scales) coexisting with conodonts, ammonoids, and bivalves were recovered from carbonates of the Pardonet, Baldonnel, Ludington, and Liard formations in the Peace River area of British Columbia. These faunas provide an excellent biostratigraphical framework for Triassic strata. Results from this study demonstrate that ichthyoliths can be used in basin analyses to date and correlate strata. The following summar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(52 citation statements)
references
References 0 publications
0
52
0
Order By: Relevance
“…An attempt is made to assess the variation by comparing it to extant and fossil shark species and to the framework of formal taxa introduced by Johns et al (1997).…”
Section: Methodsmentioning
confidence: 99%
“…An attempt is made to assess the variation by comparing it to extant and fossil shark species and to the framework of formal taxa introduced by Johns et al (1997).…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies (Pla et al, 2009;2013) on isolated teeth from the same samples that the scales of this study identified the following tooth based species: Palaeobates angustissimus (Agassiz, 1838), Pseudodalatias henarejensis Botella, Plasencia, Márquez-Aliaga, Cuny and Dorka, 2010; Hybodus bugarensis Pla, Márquez-Aliaga and Botella, in press; Prolatodon bucheri (Cuny, Rieppel and Sander, 2001); Prolatodon contrarius (Johns, Barnes and Orchard, 1997); Hybodus plicatilis Agassiz, 1838; and Lissodus aff. lepagei (Fig.…”
Section: Correlation With Fossil Teethmentioning
confidence: 99%
“…The Hydriot denticle compares favorably to the par-agenus Moreyella (Gunnell, 1933;Hansen, 1986), which has been tentatively affiliated with Carboniferous-Permian hybodontiform chondrichthyans (e.g., Derycke-Khatir et al, 2005). The Triassic paragenera Fragilicorona and Labascicorona (Johns et al, 1997) also display very similar, tricuspid distal crowns like the denticle in question, but their systematic affinities beyond the euselachian level have not been discussed (Ivanov et al, 2013). Hybodontiform dermal denticles can exhibit disparous morphologies, even in the same individual, ranging from somewhat stockier and shorter types with more keels and stout or undeveloped necks (Reif, 1978), to more delicate and elongate ones like AMPG 551.…”
Section: Systematic Paleontologymentioning
confidence: 99%
“…Remarks. The presence of a slender crown with three keels on its anterior surface and a narrow neck are common features in scales of PaleozoicMesozoic ctenacanthids, but are also common in euselachian chondrichthyans (Reif, 1978;Hansen, 1986;Rieppel et al, 1996;Johns et al, 1997;Derycke-Khatir et al, 2005;Ivanov et al, 2013). The Hydriot denticle compares favorably to the par-agenus Moreyella (Gunnell, 1933;Hansen, 1986), which has been tentatively affiliated with Carboniferous-Permian hybodontiform chondrichthyans (e.g., Derycke-Khatir et al, 2005).…”
Section: Systematic Paleontologymentioning
confidence: 99%